A Novel ZnF2-Catalyzed Esterification of Oleic Acid - Niu, Pingping; Zhao, Weihao; Jiang, Guofang; Guo, Cancheng (Asian Journal of Chemistry, 2014)
Esterification reactions of oleic acid with alcohols have been performed by using zinc fluoride as catalyst. High conversion and good yields were obtained. In this study, the influence of various reaction parameters such as reaction time, catalyst loading and mole ratio of starting materials were investigated. With a mole ratio of oleic acid to glycerol of 3.4, 15 wt % zinc fluoride added and the reaction were completed smoothly at 170 °C for 8 h with good yield of 81.9 % and the esterification rate reached 97.5 %. The ester was easily separated from the reaction mixture and the zinc fluoride used could be recycled and reused at least five times without obvious loss of catalytic efficiency.